Unlocking the Fluorine‐Free Buoy Effect: Surface‐Enriched Ruthenium Polypyridine Complexes in Ionic Liquids - Sanchez Merlinsky, Luciano (2024)
Controlling the local concentration of metal complexes at the surface of ionic liquids (ILs) is a highly sought-after objective due to its pivotal implications in supported ionic liquid phase (SILP) catalysis. Equally important is to avoid per- and polyfluorinated substances due to environmental concerns. Herein, we investigate the surface enrichment of Ru polypyridyl complexes with fluorine-free alkylic side groups of varying lengths and shapes, using the hydrophilic IL [C2C1Im][OAc] as solvent. Additional charged carboxylate groups are included into the polypyridyl ligands to increase the solubility of the complex in the IL. When the ligand system is functionalized with long and hydrophobic alkyl side chains, the complex predominantly localizes at the IL/vacuum interface, as deduced from angle-resolved X-ray photoelectron spectroscopy. Conversely, in the presence of short or more bulky substituents, no surface enrichment is observed. This buoy-like behaviour with fluorine-free side groups is explored for 0.05 %mol to 1 %mol solutions. Intriguingly, surface saturation occurs at approximately 0.5 %mol, which is beneficial to the efficient operation of catalytic systems featuring high surface areas, such as SILP catalysts.